Biochemical and Molecular Characterization of Escherichia coli from Poultry Intestine and Feces in Dinajpur, Bangladesh - Shahanavaz, Md; Husneid, Md; Mahatab, T. (Nepalese Journal of Agricultural Sciences, 2026)
Escherichia coli (E. coli) in poultry presents a significant zoonotic concern, as certain pathogenic strains particularly ETEC (Enterotoxigenic Escherichia coli) can be transmitted from poultry to humans through direct contact, environmental contamination, or the food chain, especially via undercooked poultry meat or contaminated produce. The objective of this study was to separate, biochemically identify, and molecularly characterize E. coli from samples of poultry feces and intestine. A total of 150 samples (50 intestinal, 100 feces) were collected from Dinajpur broiler farms and transported to the Department of Microbiology, HSTU, Dinajpur, in an ice box with PBS while maintaining aseptic conditions. In Nutrient Agar Colonies were observed and further sub cultured on MacConkey agar and then on selective media Eosin Methylene Blue Agar (EMB agar) at 37°C for 24 hours before undergoing biochemical tests such as Motility indole Urease (MIU), Simmons citrate, Indole, Methyl Red and Triple sugar Iron (TSI) utilization. Bacterial confirmation was performed followed by PCR-based confirmation including genomic DNA isolation and gel electrophoresis. Isolates confirmed as E. coli were serotyped and further characterized by Polymerase Chain Reaction (PCR) targeting the E. coli primer gene. The overall prevalence of E. coli was 69.33 %, with a higher isolation rate from fecal samples (73%) than intestine samples (62%). There weren't many samples used for PCR. PCR produced bands that were positive during the analysis. In the future, more intestinal and fecal samples from different areas will be examined for research purposes.